2012
DOI: 10.1128/aem.05584-11
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequences and Characterization of the Related Gordonia Phages GTE5 and GRU1 and Their Use as Potential Biocontrol Agents

Abstract: Activated sludge plants suffer frequently from the operational problem of stable foam formation on aerobic reactor surfaces, which can be difficult to prevent. Many foams are stabilized by mycolic acid-containing Actinobacteria, the mycolata. The in situ biocontrol of foaming using phages is an attractive strategy. We describe two polyvalent phages, GTE5 and GRU1, targeting Gordonia terrae and Gordonia rubrupertincta, respectively, isolated from activated sludge. Phage GRU1 also propagates on Nocardia nova. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…Similar repeat structures have been observed in Tsukamurella phage TPA2 (15) as well as in other mycolata phages (21), where similar hypotheses have been proposed for their possible functions.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Similar repeat structures have been observed in Tsukamurella phage TPA2 (15) as well as in other mycolata phages (21), where similar hypotheses have been proposed for their possible functions.…”
Section: Resultssupporting
confidence: 56%
“…A similar level of stringent strain specificity has been observed in other actinophages (15)(16)(17)(18)(19)(20)(21)27). Possible explanations include an absence of a compatible receptor site in the resistant host cell, absence of appropriate molecular machinery to support infection, or possession of phage resistance systems like clustered regularly interspersed repeat (CRISPR) systems, restriction modification (RM) systems, and abortive infection (Abi) systems (28).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…However, they were considered a single product since the concatenated gene products present homology with single proteins from other systems. It was recently suggested that they were once encoded by a single gene or possibly fused in other systems (97). Second, the phages Enterococcus phiEf11, Microcystis Ma-LMM01, Streptococcus M102, Thermus P23-77, and Synechococcus CBS2 and SPM2 encode two predicted endolysins often found in adjacent genes and proximate to the putative holin ORF.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the use of phages in engineered applications, phages may be an advantageous option for inactivating the filamentous bacteria responsible for foaming and sludge bulking, because they can specifically target the desired organisms (Choi et al, 2011;Petrovski et al, 2012;Thomas et al, 2002). Since phages are autocatalytic, and the phage concentration increases after cellular lysis, the return sludge may be used to produce a continual supply of phages, which may control the long-term overgrowth of filamentous bacteria.…”
Section: Introductionmentioning
confidence: 98%